Remote Laboratory for Cybersecurity of Industrial Control Systems. Issue 29 (2015) - Canto, Carlos J. Del; Prada, Miguel A.; Fuertes, Juan J.; Alonso, Serafín; Domínguez, Manuel
Abstract: The increasing application of information and communication technologies (ICT) to industrial control systems has improved the scalability and flexibility of these systems, enabling the possibility to access them from external nodes. However, in many cases, the evolution of these elements has exposed industrial control systems (ICS) to a series of threats for which they are usually unprepared. These systems are currently found not only in industrial settings but also in all kinds of critical infrastructures. For that reason, it is essential to promote education in the field of cybersecurity for industrial control systems, being hands-on experience the most important aspect. In this work, we present a remote laboratory that enables performing cybersecurity tests on real industrial control elements. This platform consists of a test environment that has been added to our remote laboratory of automatic control (LRA-ULE), and lets students work with industrial equipment used in real installations such as PLCs, gateways or electrical meters. The communications architecture is based on a three-layer structure (physical, server and client layer), which is also used in the rest of the LRA-ULE platform. Moreover, a web-based front-end to interact with the system and a set of practical tasks have been developed, so that students can learn to configure and run a vulnerability scanner or to interpret vulnerability reports.